The myopia of learning - Levinthal, Daniel A.; March, James G. (Strategic Management Journal, 1993)
Organizational learning has many virtues, virtues which recent writings in strategic management have highlighted. Learning processes, however, are subject to some important limitations. As is well-known, learning has to cope with confusing experience and the complicated problem of balancing the competing goals of developing new knowledge (i.e., exploring) and exploiting current competencies in the face of dynamic tendencies to emphasize one or the other. We examine the ways organizations approach these problems through simplification and specialization and how those approaches contribute to three forms of learning myopia, the tendency to overlook distant times, distant places, and failures, and we identify some ways in which organizations sustain exploration in the face of a tendency to overinvest in exploitation. We conclude that the imperfections of learning are not so great as to require abandoning attempts to improve the learning capabilities of organizations, but that those imperfections suggest a certain conservatism in expectations.